Comparative analysis of antifungal, antioxidant and cytotoxic activities of mycosynthesized silver nanoparticles and gold nanoparticles. (12th May 2022) - BalaKumaran, M.D.; Ramachandran, R.; Balashanmugam, P.; Jagadeeswari, S.; Kalaichelvan, P.T.
ABSTRACT: This study aimed to compare the antifungal, antioxidant and cytotoxic activities of Aspergillus terreus mediated silver nanoparticles (AgNPs) with that of gold nanoparticles (AuNPs). AgNPs were spherical in shape with a size of 8–20 nm; whereas, AuNPs showed anisotropic morphology (10–50 nm). Interestingly, AgNPs showed excellent antifungal activity against all the plant pathogens tested; while, AuNPs did not show any inhibition. However, both these nanoparticles showed good antioxidant activities. Among six different cancer cell lines tested, AgNPs showed comparatively significant cytotoxicity against MCF-7 cells with an IC50 value of 2.90 μg/mL; whereas, AuNPs showed the maximum activity against HepG2 cells (IC50 : 25.79 μg/mL). Acridine orange-ethidium bromide (AO-EB) dual staining and nucleic acid staining (DAPI) confirmed the apoptotic phenomenon induced by nanoparticles, which was further confirmed by cell cycle analysis. Taken together, myco-derived AgNPs can be considered for potential biomedical and agricultural applications after thoroughly analysing their toxicity. GA: uf0001